Human health risk assessment and source diagnosis of polycyclic aromatic hydrocarbons (PAHs) in the corn and agricultural soils along main roadside in Changchun, China. Issue 3 (2nd April 2016) - Chen, Yanan; Zhang, Jiquan; Ma, Qiyun; Sun, Caiyun; Ha, Si; Zhang, Feng
ABSTRACT: This work was to investigate distribution characteristics, human health risk assessment, and possible sources of 16 priority polycyclic aromatic hydrocarbons (PAHs) in corn and surface soils of farmlands along main roadside in Changchun City, Jilin Province, China. Total concentrations of 16 PAHs ranged from 1572.4 to 4390.2 µg/kg with a mean value of 2954.9 µg/kg in soils and from 219.9 to 627 µg/kg with a mean value of 362µg/kg in corn. Light-molecular-weight PAHs (2–3 rings) concentration was dominant in soils, accounting for 51%, whereas high-molecular-weight PAHs (5–6 rings) concentration was highest in corn, accounting for 48%. The results of plant concentration factor indicated that high-molecular-weight PAHs have greater mobility. To evaluate potential risk to human health, hazard index (HI) and risk index (RI) were employed. The values of HI for corn and soils were both smaller than 1, indicating that exposure of PAHs posed no or little potential risk to local residents. The fact that values of RI for corn and soils were smaller than 1 × 10 –4 suggested that exposure of PAHs posed no or little cancer risk to local residents. The possible sources of PAHs in corn and soils were both identified as mixture patterns of pyrogenic and petrogenic sources.